2006
DOI: 10.1007/s00520-006-0034-9
|View full text |Cite
|
Sign up to set email alerts
|

Neutropenic event risk and impaired chemotherapy delivery in six European audits of breast cancer treatment

Abstract: NEs occurred frequently in this combined dataset and they affected treatment delivery. Identifying patients at high NE risk enables targeted prophylaxis and may avoid dose limitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 21 publications
3
51
1
2
Order By: Relevance
“…Although the risk of fn for several chemotherapy regimens has been widely described within the context of clinical trials, only a few studies have described the occurrence of fn in clinical practice [19][20][21][22][23] . Interestingly, the reported incidence of fn associated with specific chemotherapy regimens is higher in clinical practice than in clinical trials 19,21,[23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…Although the risk of fn for several chemotherapy regimens has been widely described within the context of clinical trials, only a few studies have described the occurrence of fn in clinical practice [19][20][21][22][23] . Interestingly, the reported incidence of fn associated with specific chemotherapy regimens is higher in clinical practice than in clinical trials 19,21,[23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…High-quality therapy results from the fact that dose reductions or interval prolongation were stated in less than 10% of cases, which implies a high relative dose intensity of the chemotherapy conducted. This is an important indicator for the quality of therapy [6]. The high rate of available predictive factors (ER, PR HER2) is proof of a positive implementation of an evidence-based approach.…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10] FN is associated with significant morbidity and mortality, with estimates of 6.8% to 20% mortality among patients who are hospitalized for FN-related complications and with higher rates observed in patients who have major comorbidities and documented sepsis or shock. 2,[10][11][12] FN and Late Mortality Despite successful management, FN may have an equally important impact on the overall chemotherapy treatment plan, resulting in dose reductions, treatment delays, chemotherapy discontinuation, or a switch to alternative, less toxic, or potentially less effective regimens. 11,13 Myelosuppression continues to represent the major cause of reduced chemotherapy dose intensity.…”
Section: Fn and Early Mortalitymentioning
confidence: 99%
“…2,[10][11][12] FN and Late Mortality Despite successful management, FN may have an equally important impact on the overall chemotherapy treatment plan, resulting in dose reductions, treatment delays, chemotherapy discontinuation, or a switch to alternative, less toxic, or potentially less effective regimens. 11,13 Myelosuppression continues to represent the major cause of reduced chemotherapy dose intensity. In vivo animal studies have demonstrated that relatively small decreases in dose can cut cure rates by 50% or more.…”
Section: Fn and Early Mortalitymentioning
confidence: 99%